FROM COLONIAL DOMINATION TO THE MAKING OF THE NATION: ETHNO-RACIAL CATEGORIES IN CENSUSES AND REPORTS AND THEIR POLITICAL USES IN BELIZE, 19TH-20TH CENTURIES. - Cunin, Elisabeth; Hoffmann, Odile (Caribbean Studies)
This paper presents an analysis of the processes of classification and racial-ethnic categorization of Belize's population during the 19th and 20th centuries, based on population censuses and government reports. We are not too interested in figures as such but in the categories of counting and their evolution, as indicators of the political rationale of building a colonial and later a national society. While the censuses for the 19th century relate to different forms of population management (transition from slavery to freedom, affirmation or denial of ethnic and racial diversity), the administrative reports paint a static and stereotyped demographic-territorial model as a tool of the political project. For the 20th century, we analyze the difficult road to independence and the changes introduced by the new Belizean state (categories, methods) in the process of creating a "national identity."